Intrapersonal and Stress Management Dimensions of Emotional Intelligence as Determinants of Mathematics Performance - Odicta, Giena L. (JPAIR Institutional Research, 2016)
Students’ success in mathematics instruction is determined by some school and personal measures and most likely, quality emotions and feelings that could also help students. The descriptive-correlational research ascertained the students’ level of emotional intelligence and its association to mathematics performance. Using Sta. Maria’s (2007) Emotional Intelligence Inventory, data were gathered from the 222 college students of Capiz State University, Philippines selected through simple random sampling. Data were analyzed using the mean, Pearson’s Product Moment of Correlation and ANOVA. The results of the study showed that college students had an average level of emotional intelligence. The students’ mathematics performance was good. The study also revealed that sibling rank shows significant relationship with emotional intelligence. Intrapersonal and stress management measures were strongly associated with students’ performance in the mathematics. Class size and time of class significantly influenced the mathematics performance of students. The need to stress management on emotional intelligence is, therefore, vital to promote classroom learning.